2023
DOI: 10.1038/s41699-023-00420-1
|View full text |Cite
|
Sign up to set email alerts
|

Twist angle dependent interlayer transfer of valley polarization from excitons to free charge carriers in WSe2/MoSe2 heterobilayers

Frank Volmer,
Manfred Ersfeld,
Paulo E. Faria Junior
et al.

Abstract: Transition metal dichalcogenides (TMDs) have attracted much attention in the fields of valley- and spintronics due to their property of forming valley-polarized excitons when illuminated by circularly polarized light. In TMD-heterostructures it was shown that these electron-hole pairs can scatter into valley-polarized interlayer exciton states, which exhibit long lifetimes and a twist-angle dependence. However, the question how to create a valley polarization of free charge carriers in these heterostructures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 91 publications
(178 reference statements)
0
6
0
Order By: Relevance
“…We attribute the observed IX emission to K-K transition in the mentioned samples (also illustrated in figure 1(c)). Considering the stacking order of the investigated samples, MoSe 2 sustains similar strain with changing twist angle which leads to the Q valley being energetically above the K valley in CB, as MoSe 2 is in contact with substrate [21,35]. Thus, IX formation and relaxation in the studied samples mainly happen through the momentum direct K-K transition.…”
Section: Twist Angle-dependent Anomalous Optical Responsementioning
confidence: 90%
See 2 more Smart Citations
“…We attribute the observed IX emission to K-K transition in the mentioned samples (also illustrated in figure 1(c)). Considering the stacking order of the investigated samples, MoSe 2 sustains similar strain with changing twist angle which leads to the Q valley being energetically above the K valley in CB, as MoSe 2 is in contact with substrate [21,35]. Thus, IX formation and relaxation in the studied samples mainly happen through the momentum direct K-K transition.…”
Section: Twist Angle-dependent Anomalous Optical Responsementioning
confidence: 90%
“…Nevertheless, the band offset can be manipulated by altering the Fermi level of the individual materials layers at thermal equilibrium by, for instance, varying the local density of carriers (e.g. electrostatic doping) [35,[44][45][46][47]. In the TMDC material family, further aspects must be considered when studying a heterojunction formed by few-or mono-layers.…”
Section: Band Offset Modulation Based On Twist Anglementioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 presents the calculated band structures for six different M 6 B 6 T 6 sheets. The band structures revealed that all sheets exhibit metallic characteristics, similar to borophene [62] and some MXenes such as V 2 C and Nb 2 C [63] . The band dispersions of M 6 B 6 T 6 were strongly affected by the surface terminals and different metal elements.…”
Section: Electronic Propertiesmentioning
confidence: 93%
“…During the stacking, the crystal orientation is a key factor. This is because the properties of t-TMDCs are closely related to the relative orientation between the two layers [25]. Thus, it is essential to understand and control the crystal orientation of the involved monolayer before stacking.…”
Section: Physical Methodsmentioning
confidence: 99%